Chromatographic Analysis Technique for the Determination of Phenolic Compounds in Brassica oleracea L.var capitata - Ahmad, Fazil; Mohamed, Jamal Moideen Muthu (Challenges and Advances in Pharmaceutical Research Vol. 8, 2022)
Brassica foods are particularly nutrient-dense, offering vitamins, carotenoids, fibre, soluble sugars, minerals, glucosinolates, and phenolic compounds, among other nutrients and health-promoting phytochemicals. The current knowledge indicates that the aging processes may result from oxidative stress leading to a variety of alterations within the human organism caused by Reactive Oxygen Species (ROS). In the present work, high-performance liquid chromatography was used to assess the phenolic compounds rutin, quercetin, and kaempferol in Brassica oleracea L.var capitata (HPLC).For the estimation of Rutin, Quercetin and Kaempferol by HPLC method, the mobile phase used are, Acetonitrile and Phosphate buffer (pH=5.8) in ratio of 55: 45. Quantification of Rutin, Quercetin and Kaempferol was carried by Athena C18 column and absorbance was measured at 254 nm with flow rate of 1 ml/min. In HPLC analysis the retention time (Rt) of standards, Rutin, Quercetin and Kaempferol were found to be 2.357, 6.093 and 9.373 respectively, while the Retention times of Rutin and Kaempferol in Brassica oleracea L.var capitata are 2.387, 6.060 and 9.113 which are found to be matching with standards retention time values respectively. In comparison to other approaches, the cost and running time per analysis are determined to be cheap. So, rutin, quercetin, and kaempferol can all be quantitatively analysed using this method. The procedure was discovered to be quick, effective, and straightforward and can be used as quality control for phenolic chemicals (rutin, quercetin, and kaempferol).